One hundred shinning candles - Lunn, Janet; Grater, Lindsay (New York : Macmillan Publishing, 1991)
Ten-year-old Lucy is a pioneer girl in the Upper Canada of 1800. Her imagination fired by the schoolmaster$1 (Bs stories of Christmas memories, Lucy sets about making a special Yuletide gift $1 (Bsomething her frail mother will be able to remember and cherish forever. But even with the unwelcome help of her little brother, Dan, making one hundred handmade candles to light on Christmas night is a daunting task. Limited supplies and resources make the job that much harder, but in the end it is Lucy$1 (Bs own bossiness that nearly causes a disaster. Deeply disappointed in herself, Lucy accepts the sacrifice Dan offers to make, and together the children manage to create the most wonderful of all Christmases. s